About the material a priori of Phenomenology - Ruiz Fernández, José (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
It is my intention to elucidate what are the foundations of the truth of those propositions that express what the phenomenological tradition since Husserl has called a «material a priori». My aim is not to paraphrase Husserl, but to try to specify the evidence we have of such claims. I aim to consider to what extent at the basis of such an evidence lays linguistic meaning and how the traditional phenomenological understanding of that evidence may be improved resorting to ideas that are close in spirit to the latter Wittgenstein.